Dimensions of binding and non-binding social responsibility and its relationship to organizational performance / Field Study in telecommunications companies in the Republic of yemen - الجناعي نوري عبد الودود; حسن عبد الله جبر (Journal of Economics and Administrative Sciences, 2018)
The study aims at measuring the dimensions of binding and non-binding social responsibility and its relation to the organizational performance in telecommunication companies in the Republic of Yemen using analytical descriptive approach and questionnaire as a main tool for data collection and comprehensive inventory method. It has been found that there is a positive effect and significant moral relation between social responsibility with its binding and non-binding dimensions and the organizational performance of telecommunication companies in the Republic of Yemen at a level of significance below (0.05). It has also been found that the correlation between the non-binding social responsibility and the ethical dimension is a highly significant and positive and medium in the human dimension. A positive correlation has been noticed between binding social responsibility and the economic and legal dimension of the Organizational performance. The level of corporate social responsibility commitment was significant. This is represented in the legal, and the economic dimension. This is followed by the non-binding social responsibility which is represented mainly in the level of commitment in the ethical dimension and the humanitarian. However, the level of regulatory performance in telecommunication companies in Yemen was generally average.